VL Gehun 967: A high yielding, rust-resistant wheat (Triticum aestivum L.) variety, suitable for rainfed organic conditions of Uttarakhand hills of India - Kant, Lakshmi; Jain, Sanjay Kumar; Raghu, Borehalli Rangaswamy; Mahanta, Dibakar (Journal of Cereal Research, 2021)
VL Gehun 967 is a rust resistant high yielding variety, released by Uttarakhand seed Sub-Committee and further notified by Central Sub-Committee on Crop Standards, Notification and Release of Variety. It has been recommended for cultivation under rainfed organic timely sown production conditions of Uttarakhand hills. VL Gehun 967 recorded an average grain yield of is 1.97 t ha-1, which is 12.71% higher than the best check VL Gehun 907. This variety has recorded maximum average coefficient of infection (ACI) of 17.4 for stripe rust and 4.0 for leaf rust under artificial inoculation conditions indicating that it is resistant to both stripe and brown rust. It possesses 9.78 to 10.07% average protein, 76.37 to 79.73 kg/hl-1 hectoliter weight and 7.63 to 7.56 very good chapatti quality score, therefore, possessing very good quality for chapatti making and good flour recovery. The large scale cultivation of this variety in Uttarakhand hills under organic conditions would enhance wheat productivity and also help in reducing the inoculum load of rusts in hills of Uttarakhand due to its better resistance.